Protective effects of Lizhong decoction on ulcerative colitis in mice by suppressing inflammation and ameliorating gut barrier. (15th September 2020) - Shen, Yumeng; Zou, Junfeng; Chen, Mengjun; Zhang, Zhimiao; Liu, Chen; Jiang, Shu; Qian, Dawei; Duan, Jin-Ao
Abstract: Ethnopharmacological relevance: Lizhong Decoction (LZD) is a classical prescription firstly recorded in "Shanghan Lun". It has been used to clinically treat ulcerative colitis (UC) for thousands of years. However, its mechanism is not clear up to now. Aim of the study: The goal of this study was to assess the amelioration of LZD on dextran sodium sulfate (DSS)-induced colitis in mice and further clarify its mechanism. Materials and methods: The ulcerative colitis model induced by DSS was successfully established and applied to evaluate the intervention effect after oral administration of LZD. Furthermore, the expression of key targets in inflammatory signaling pathways and intestinal tight junction proteins were investigated by enzyme-linked immunosorbent assay (ELISA) and quantitative real time polymerase chain reaction (qPCR) analysis. Results: The results showed that all doses of LZD could notably improve DSS-induced colon lesions, reduce histological scores, prolong colon length and increase body weight. Colonic inflammation in UC mice was significantly alleviated by inhibiting the activities of myeloperoxidase (MPO) and superoxide dismutase (SOD), reducing the yield of nitric oxide (NO) and inflammatory cytokines such as interferon-γ (IFN-γ), tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and interleukin-6 (IL-6), and along with promoting the production of anti-inflammatory cytokines such as interleukin-4 (IL-4) and interleukin-10 (IL-10) after LZD treatment. Furthermore, LZD remarkably down-regulated the level of toll-like receptor 4 (TLR4) and nuclear factor-κB (NF-κB) mRNA and up-regulated the expression of tight junction proteins (zonula occluden-1, occludin and claudin-1) in UC mice. Conclusion: In summary, this study indicated that LZD could notably improve UC symptoms by suppressing inflammation and ameliorating gut barrier, which provided scientific basis for its clinical application in the future. Graphical abstract: Image 1